(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
Well-being is a core topic of research in the positive psychology, but. there are very few investigations that illuminate subjective well-being (SWB) and related concepts in Macedonian cultural context. The aim of this study was to examine whether dominant orientation tOM’ard past, present or future can predict subjective well-being among Macedonian university students. ZTPJ was distributed to 252 students ranging in age from 18 to 27. The cognitive aspect of subjective well-being was measured with SWLS, while the data for affective aspect of subjective well-being were obtained with PANAS. The results generally approved the hypothesis showing that students with sentimental attitude toward past had a more positive affect and satisfaction with life, accompanied with lower negative affect. Also, orientation toward present pleasure was related to more positive affect and satisfaction with life. Participants with dominant Past- Negative perspective were more likely to experience negative affect along with lower level of life satisfaction and positive affect. The fatalistic view of the present was associated with negative affect, while future orientation with satisfaction with life. The findings emphasize the relevance of time perspective styles for the SWB, especially Past-Positive, Present-Hedonistic and avoidance of Past-Negative, which appeared to be significant predictors in Macedonian context.